Manajemen Pariwisata Berbasis Masyarakat Sebagai Strategi Pengembangan Pariwisata Berkelanjutan - Adelismula, Riska Julianti (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study seeks to describe the implementation of community-based tourism management principles at the Beringin Kembar Dam Tourism Object in Marente Village, Alas District, Sumbawa Regency, as well as to identify the supporting and inhibiting factors affecting its development. The research employed a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The informants consisted of village officials, tourism managers, and community members directly involved in tourism activities. Data analysis followed the stages of data reduction, presentation, and conclusion drawing, with validity ensured through triangulation of sources and methods. The findings reveal that the tourism management in Marente Village has applied the four main management functions: planning, organizing, implementing, and controlling. The village government, local community, and Tourism Awareness Group (Pokdarwis) actively collaborate in each stage of tourism activities. Supporting factors include the village’s natural potential, strong community participation, and the government’s facilitative role, while inhibiting factors consist of limited infrastructure, low visitor awareness of cleanliness, and inadequate digital promotion. Overall, the implementation of CBT in Marente Village contributes to economic empowerment, cultural preservation, and the realization of inclusive and sustainable tourism at the local level.